2019
DOI: 10.1021/acsmedchemlett.9b00420
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective MTH1 Inhibitors for Oncology: Enabling Rapid Target (In)Validation

Abstract: We describe the discovery of three structurally differentiated potent and selective MTH1 inhibitors and their subsequent use to investigate MTH1 as an oncology target, culminating in target (in)­validation. Tetrahydronaphthyridine 5 was rapidly identified as a highly potent MTH1 inhibitor (IC50 = 0.043 nM). Cocrystallization of 5 with MTH1 revealed the ligand in a Φ-cis-N-(pyridin-2-yl)­acetamide conformation enabling a key intramolecular hydrogen bond and polar interactions with residues Gly34 and Asp120. Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The NUDT family of enzymes is an intriguing family of enzymes that play a key role in the progression of breast and other cancers. The therapeutic potential of NUDT-selective inhibitors has already been shown—NUDT1-selective inhibitors have shown efficacy in multiple studies in vitro and in vivo [ 67 , 68 , 69 , 70 ], and the NUDT5-selective inhibitor TH1457 blocks cell proliferation in breast cancer cells [ 71 ]. Given the interest in NUDT inhibition for the management of cancer patients, a greater understanding of the signaling pathways impinging on the activity of NUDT enzymes is required and may be facilitated by the interrogation of global phosphoproteomic and gene expression datasets ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NUDT family of enzymes is an intriguing family of enzymes that play a key role in the progression of breast and other cancers. The therapeutic potential of NUDT-selective inhibitors has already been shown—NUDT1-selective inhibitors have shown efficacy in multiple studies in vitro and in vivo [ 67 , 68 , 69 , 70 ], and the NUDT5-selective inhibitor TH1457 blocks cell proliferation in breast cancer cells [ 71 ]. Given the interest in NUDT inhibition for the management of cancer patients, a greater understanding of the signaling pathways impinging on the activity of NUDT enzymes is required and may be facilitated by the interrogation of global phosphoproteomic and gene expression datasets ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The original interest in pharmacological modulation of NUDIX members was sparked by the notion that NUDT1 is overexpressed in several cancer cell types, while its role in healthy cells can largely be compensated for as evidenced by the normal life-span of knock-out mice (Tsuzuki et al, 2001). Besides GTP and dGTP, NUDT1 hydrolyzes several oxidatively damaged DNA nucleotides including 8-oxo-dGTP and 2-OH-dATP, thus preventing their incorporation into DNA, which FIGURE 1 | Published NUDIX inhibitors: TH588 was developed as a first in class NUDT1 inhibitor at Science for Life Laboratory and Karolinska Institutet (Gad et al, 2014); (S)-Crizotinib is a potent NUDT1 inhibitor and the enantiomer of (R)-Crizotinib (Huber et al, 2014), a clinically applied tyrosine kinase inhibitor; optimized by Astra-Zeneca; AZ-15, AZ-21 and AZ-24 are distinct chemotype inhibitors targeting NUDT1 (Kettle et al, 2016); BAY-707 (Ellermann et al, 2017) was discovered as a NUTD1 inhibitor by Sprint Bioscience; IACS-4759 (Petrocchi et al, 2016) is a NUDT1 inhibitor developed by MD Anderson; MI-743 is a selective inhibitor of NUDT1 in gastric cancers (Zhou et al, 2019); Compound 5 was reported by Gilead and inhibits NUDT1 (Farand et al, 2020); TH5427 was synthesized as a lead compound against NUDT5 (Page et al, 2018); NUDT7-COV-1 is a covalent inhibitor generated by electrophile screening and fragment combination (Resnick et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This led to the hypothesis that increased expression of NUDT1, and hence improved sanitization capacity of oxidatively damaged DNA bases from the nucleotide pool, would enable cancer cells to cope with the increased oxidative stress they are exposed to compared with healthy cells. Gad and coworkers published TH588 (Figure 1) as the first small-molecule NUDT1 inhibitor with efficacy in mouse xenograft models (Gad et al, 2014), although subsequent potent and selective NUDT1 inhibitors disclosed by AstraZeneca, MD Anderson, Gilead and Sprint Bioscience/Bayer failed to reproduce these findings with regards to cytotoxicity (Figure 1) (Kettle et al, 2016;Petrocchi et al, 2016;Ellermann et al, 2017;Farand et al, 2020). The validity of NUDT1 as an anticancer target has thus been questioned and is still under debate (Warpman Berglund et al, 2016;Samaranayake et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During this research, several potent MTH1 inhibitors have been synthesized and validated, including Tetrahydronaphthyridine 5 ( IC 50 = 0.043 nM) [ 30 ], BAY-707 ( IC 50 = 2.3 nM) [ 31 ], and other compounds [ 32 ]. Although these compounds exhibit a much higher affinity compared with existing inhibitors, none of them show potent cancer-killing efficacy, casting doubts on the potential of MTH1 to provide effective cancer treatment drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the possibility of killing cancer cells through targeting MTH1 is still controversial [ 30 , 31 , 32 ], a promising yet unexplored application of MTH1 inhibitors is to monitor disease progression that involves oxidative stress since elevated oxidative stress in cells occurs in a large number of chronic diseases including different types of cancers.…”
Section: Discussionmentioning
confidence: 99%